A new approach to dose reference levels in pediatric CT: Age and size-specific dose estimation. (April 2023) - Rawashdeh, Mohammad; Saade, Charbel; Al Mousa, Dana S.; Abdelrahman, Mostafa; Kumar, Praveen; McEntee, Mark
Abstract: Background: Although paediatrics' are more radio-sensitivity than adults, the number of requested paediatric CT examinations is increasing globally. Significant efforts have been focused on achieving the lowest possible radiation dose for paediatric patients, particularly adjusting for size differences. This study aims to establish Diagnostic Reference Levels (DRLs) for paediatric patients based on size-specific dose estimates (SSDE). Method: In this retrospective national study, CT scans for brain, chest, abdominopelvic, and chest, abdomen, and pelvis (CAP) were collected from four hospitals in Jordan undergoing paediatric CT scans. A total of 1818 cases were randomly selected in four age categories (<1 year, 1–4 years, 5–10 years, 11–18 years). The SSDE values were determined by multiplying the volume CT dose index (CTDIvol ) with the conversion factor extracted from the American Association of Physicists in Medicine Report 204. Results: Variations exist between the DRLs between the different hospitals, age groups, and variations in protocols with different types of CT scanners. The DRL values (CTDIvol, dose-length product (DLP) and SSDE) for the four age categories were as follows; <1 year: brain (47.88 mGy, 741.67 mGy cm and 58.40 mGy), chest (5.65 mGy, 124 mGy cm and 13.91 mGy), abdominopelvic (12.65 mGy, 321.5 mGy cm and 28.72 mGy) and CAP (16.12 mGy, 507.72 mGy cm and 38.04 mGy). 1–4 years, brain (54.79 mGy, 979.12 mGy cm and 55.88 mGy), chest (7.37 mGy, 220.85 mGy cm and 14.68 mGy), abdominopelvic (16.16 mGy, 424.72 mGy cm and 32.68 mGy) and CAP (16.13 mGy, 742.1 mGy cm and 33.54 mGy). 5–10 years: brain (65.03 mGy, 1129.94 mGy cm and 55.92 mGy), chest (12.57 mGy, 383.9 mGy cm and 22.45 mGy), abdominopelvic (12.34 mGy, 450.75 mGy cm and 22.23 mGy) and CAP (13.46 mGy, 748.85 mGy cm and 25.69 mGy). 11–18 years, brain (60.7 mGy, 1207.9 mGy cm and 41.81 mGy), chest examination (12.94 mGy, 496.2 mGy cm and 20.49 mGy), abdominopelvic (16.13 mGy, 803.07 mGy cm and 23.06 mGy) and CAP (16.13 mGy, 1101.5 mGy cm and 23.85 mGy). Conclusion: There were increases in CTDIvol, DLP, and SSDE with ascending age groups. SSDE and age are closely matched to delivered radiation in paediatric CT; however, radiation dose levels remain high in Jordan. This work highlights the need for caution when administering radiation in the paediatric population. Highlights: There are several sites that are implementing age-specific CT scanning protocols. There is a lack of standardization for the existing paediatric scanning protocols. The variations between the age groups could be attributed to several reasons. Various strategies should be considered to reduce the SSDE in CT scans.